Answer:
b= -10
Step-by-step explanation:
9^ -8 * 9^ -2
We know that a^b * a^c = a^ (b+c)
9^ (-8+-2)
9^ -10
We want it in the form a^b
a=9
b= -10
Happy to help :-)
Please provide us with questions
Step-by-step explanation:
Find the Center and Radius (x-4)^2+y^2=4
(
x
−
4
)
2
+
y
2
=
4
This is the form of a circle. Use this form to determine the center and radius of the circle.
(
x
−
h
)
2
+
(
y
−
k
)
2
=
r
2
Match the values in this circle to those of the standard form. The variable
r
represents the radius of the circle,
h
represents the x-offset from the origin, and
k
represents the y-offset from origin.
r
=
2
h
=
4
k
=
0
The center of the circle is found at
(
h
,
k
)
.
Center:
(
4
Answer: h=4/6
Step-by-step explanation:
6h=8-4
6h=4 /:6
h=4/6
Answer:
9
Step-by-step explanation:
18 ÷ 6 × [1] + 6
18 ÷ 6 + 6
3 + 6
9